Studying history by correspondence : assessment of the work at the Graaff-Reinet College for Continued Education - Van Niekerk, Clive (Rhodes University, Faculty of Education, Department of Education, 1989)
The aim of this study was to carry out an investigation of history as a correspondence subject for practising teachers and to make an assessment of work at the Graaff- Reinet College for Continued Training. The problems experienced by lecturers and students involved with the study of history at this institution receive particular attention. At intervals throughout the study attention is given to the need for further training for teachers who are in- service. Teacher qualifications in the Cape Province are also examined to see potential needs for further training in the future. Having determined a need, it is proposed that correspondence courses are best suited to cater for it. A study is made of the models, background and approaches used by other institutions in various parts of the world. Distance education started in England at the end of the eighteenth century. This idea has spread to various countries and today teaching and learning by correspondence takes place in most countries of the world. It is different to conventional classroom education and thus has certain unique characteristics. The definition, characteristics, background and methodology are important if the problems involved are to be understood. These aspects indicate how effective and popular this form of study has become. Particular attention is given to the teaching of in-service teachers who are upgrading their qualifications. The existing and proposed College history syllabi are examined in as far as their appropriateness and relevance are concerned. Emphasis is given to history at Graaff- Reinet College because the author is a history lecturer at this institution. An extended questionnaire was designed and used to collect the required data on the subjects who were from two groups of students studying history at the College, one in 1986 and one in 1987. A pilot study was done in 1986 and a more extended questionnaire was completed by the 1987 students. In chapter six the results of the questionnaire are analysed and particular attention is given to the students' background, motivation for studying and difficulties they encounter. Finally, recommendations are made about how this form of teacher upgrading can be improved and extended in the future
Keywords: History -- Study and teaching; Teachers -- In-service training -- South Africa; Distance education -- South Africa